الرمز و الدلالة في قصيدة سرحان يشرب القهوة في الكافيتيريا لمحمود درويش - جويحيف، قادة, باكر، توفيق (جامعة الوادي University of Eloued, 2019)
وظف الشاعر محمود درويش الرّموز الدّينية في قصيدته؛ حيث استدعى الشاعر شخصية المسيح كمعادل موضوعي لما يواجهه الإنسان الفلسطيني على يد المحتل من قتل وتهجير وآلام يلاقيها يوميا، ووظف أيضا سورة عمّ التي دلت على واقع مقتل روبرت كندي وهي نوع من التحدي للعالم الظالم الذي يكيل بمكيال إتجاه القضية الفلسطينية، كما استحضر الشاعر الرموز التاريخية الكبرى كحادثة السبّي البابلي لليهود على يد نبوخذ نصّر قديما جاء بها الشاعر ليعبّر من خلالها وبصيغة غير مباشرة عن اللجوء الفلسطيني، أما حطين فجاءت للدلالة على القدس المغتصبة كما وظف الشاعر التراث الميثولوجي البشري خدمة لأغراضه الشعرية؛ استحضر في هذه القصيدة رمزية العنقاء التي دلت على الخصب والبعث والتجدد بعد الاستشهاد أو النفي، ومن الرموز الموظفة في قصيدة سرحان يشرب القهوة في الكافيتيريا الرموز الطبيعية مثل البحر الذي دلّ على الموت والدّمار والمطر الذي دلّ على الدم والقتل والرصاص. استحضر درويش أيضا في قصدته رموزا صوفية كرمزية المرأة التي رمز بها للوطن، والخمر التي دلت على الحبّ والهيام في الأرض والوطن وهناك رموز خاصة وظفها الشاهر منها السّفينة والباخرة التي رمزت للغربة والسّفر، والخيمة التي رمزت على عدم الاستقرار، ورمزية الدّم الذي دلّ على الشهادة وطلب الحرية. Mahmoud Darwish used the religious symbols in his poem. The poet called the personality of Christ as an objective equivalent of what the Palestinian man faces at the hands of the occupier from the killing, displacement and pain he encounters every day. He also employs a surah that indicates the reality of the death of Robert Kennedy, a kind of challenge to the unjust world, The poet also referred to the great historical symbols such as the Babylonian Babylonian narrative of the Jews by Nebuchadnezzar in the past, in which the poet came to express in an indirect way the Palestinian resort. Hattin came to refer to the usurped Jerusalem as the poet used the mythological heritage Shri service for purposes of poetry; evoked in this poem phoenix symbolism that has shown fertility and rebirth and renewal after martyrdom or exile, One of the symbols employed in Sirhan's poem is coffee in the cafeteria, the natural symbols such as the sea, which attested to the death, destruction and rain that pointed to blood, murder and bullets. Darwish also invoked the symbols of the mystical symbolism of the woman symbolized by the country, and wine, which showed love and indecency in the land and the homeland and there are special symbols and employed by the shining ship and the ship that symbolized the foreign travel, and the tent that symbolized the instability, and symbolism of blood that testified to the certificate and Freedom
Keywords: الرمز الدلالة القصيدة; Symbol and significance and poem